Rectal cancer and the quality of life after surgery - Ponczek, Danuta; Nowicki, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2004)
Colorectal cancer (CRC) is a serious and growing problem not only in Poland but also all over the world. Each year in Poland there are 11,000 new cases of CRC and 8,000 people die. The disease accounts for 10.3% of all cancers in men and 10% in women. It is one of the most common types of cancer and second leading cause of cancer-related deaths for both men and women. Most frequently CRC is localised in the rectum. Preoperative radiation therapy and rectal resection within seven days is the recommended treatment. Surgery of the colorectal cancer involves an anterior resection or abdominal excision. An improvement in the technique by using mechanical staplers allows surgeons to perform low anterior resections more often. The abdominal excision means that the rectum and sphincters are removed and a stoma is created. In recent years however, saving sphincters and maintaining waste elimination in the usual way have become, apart from oncological criteria, the main principles of treatment for colorectal cancer. The quality of life of patients who underwent low anterior resection is not satisfactory because of the low anterior resection syndrome. These patients complain about rectal urgency, incontinence and stool soiling and frequent defecation. Only some of the patients notice improvement with time. For many authors the quality of life after surgery is as important as the good oncological and surgical outcome. The quality of life can be evaluated on the basis of the opinion of the person who examines the patient as well as based on patient’s self-assessment. There are two EORTC questionnaires for patients with cancer: QLQ-C30 and QLQ-CR38 which include questions concerning the quality of life.